2016
DOI: 10.15376/biores.11.3.7365-7376
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Chemical Extraction Treatments on Nano-scale Mechanical Properties of the Wood Cell Wall

Abstract: Chinese fir (Cunninghamia lanceolata (Lamb.) Hook) was subjected to chemical extraction treatments with sodium chlorite (NaClO2) for delignification, as well as sodium hydroxide (NaOH) at various concentrations for extracting hemicelluloses gradually. Nanoindentation tests, X-Ray diffraction (XRD), and Fourier transform Raman (FT-Raman) spectroscopy studies revealed the changes in the mechanical properties and the nanostructure of the cell wall. The X-ray analysis indicated that delignification had only a mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 17 publications
1
4
0
Order By: Relevance
“…Zimmermann et al (2007) explained that increased NaOH concentration degrades hemicellulose, and that mannose is the most vulnerable to NaOH. This was con rmed by various other studies(Zhang et al 2016, Zhao et al 2008and Barman et al 2020). …”
supporting
confidence: 76%
“…Zimmermann et al (2007) explained that increased NaOH concentration degrades hemicellulose, and that mannose is the most vulnerable to NaOH. This was con rmed by various other studies(Zhang et al 2016, Zhao et al 2008and Barman et al 2020). …”
supporting
confidence: 76%
“…In previous studies, it has been shown that cellulose is the determining factor affecting the longitudinal mechanical properties of fibers [ 26 ], while lignin contributes to the elastic modulus [ 27 ]. The study of the changes in chemical functional groups and the compositional structure of bamboo fiber bundles during different heat treatments was of great importance for the analysis of their mechanical properties.…”
Section: Resultsmentioning
confidence: 99%
“…The cell wall of wood is the substantial bearing structure of wood, where cellulose microfibrils are the reinforcing phase, whereas lignin and hemicellulose form the matrix laminate structure. The distribution of cellulose, hemicellulose, and lignin in the cell wall, the way they are bound, and the properties of the components themselves noticeably influence the cell wall and the macroscopic mechanical properties of the wood (Zhang 2011). When wood is subjected to the cyclic effects of UV radiation, water spray, and high temperatures, the cell wall structure, distribution, and binding patterns of wood are damaged, and degradation of cellulose, hemicellulose, and lignin occurs, resulting in changes in the wood testing indexes.…”
Section: Changes Of Testing Indexes Under Nondestructive Testing Methodsmentioning
confidence: 99%